Modelling OCD: a test of the inflated responsibility model. Issue 3 (31st October 2019) - Mitchell, Ryan; Hanna, Donncha; Dyer, Kevin F. W.
Abstract: Background: The Salkovskis (1999) model of obsessive compulsive disorder (OCD), which emphasizes the role of inflated responsibility, has proven highly influential in both the understanding and treatment of OCD. Aims: This study aimed to empirically test several core processes of this model. Method: The individual components of the model were measured using multiple indicators in a sample of undergraduate students ( n = 170), and confirmatory factor analyses were used to ascertain the most reliable, valid and theoretically consistent latent variables. Structural equation modelling was used to test proposed relations between latent constructs in the model. Results: The inflated responsibility model was a good fit for the data in the present sample. As predicted by the model, misinterpretations of intrusive thoughts as indicating personal responsibility fully mediated the relationships between responsibility beliefs and counterproductive safety strategies, neutralizing actions and mood changes. Conclusions: The Salkovksis (1999) inflated responsibility model of OCD is empirically supported in the present sample of undergraduate students, lending support to the proposed mechanisms in the model and supporting prior evidence.